Global Catalysts: Empowering Universities for Social Change in Developing Countries - Saaida, Mohammed (Edukasiana: Jurnal Inovasi Pendidikan, 2023)
This study examines the role of universities in promoting change in developing countries, despite facing constraints such as inadequate finance, outdated infrastructure, and the lack of comprehensive frameworks. The methodology of the study will employ a descriptive approach, focusing on direct observation and the recording of social change efforts in universities in developing countries. A selective sample will be chosen, and qualitative data will be evaluated using thematic analysis. It analyzes existing programs, provides a holistic framework for long-term social change, and investigates the role of universities in bringing about real change. This study empowers universities in low-income countries to address societal concerns using their intellectual capital, research capacity, and human resources. It examines contextual limits, best practices, and development areas, acknowledging limitations and highlighting the importance of future research for effective solutions and societal transformation in developing countries. This study explores the challenges universities face in promoting social transformation in developing nations, adding to the ongoing debate on higher education's capacity. It offers a holistic framework for long-term social change and has significant implications for policymakers, educators, and stakeholders interested in using universities' capacity for genuine social change. The study reached important results, which represented, first, a multifaceted approach to social transformation by playing a decisive role in facilitating social transformation by adopting a multifaceted approach. Then adopting a people-centered approach yields positive results, leading to positive social transformation and long-term growth. This is followed by emphasizing that global cooperation is vital and important in collaborating with global partners and international organizations in addressing complex societal issues and benefiting from diverse knowledge.